ROLE OF HUMAN DISKOIDIN DOMAIN RECEPTOR 1 IN THE PROGRESSION OF CHRONIC PYELONEPHRITIS IN CHILDREN - Kaladze, N. N.; Slobodyan, E. I. (Ukrainian Journal of Nephrology and Dialysis, 2017)
The purpose: to evaluate the role of collagen receptors Human Discoidin Domain Receptors (DDR1) as mediators of inflammation, proliferation and fibrosis in children with chronic pyelonephritis (CP), to reveal their relationship to the clinical form of the disease and the characteristics of its flow. Materials and methods: The levels of DDR1, transforming growth factor (TGF-β1), insulin-like growth factor (IGF-1) in the serum, β2 - microglobulin ( β2- MG) in the serum and urine were identified during the study of 40 children, ages 6 to 16 with CP in a state of clinical and laboratory remission. Results: Clinical and laboratory remission HP was associated with significant increased levels of DDR1 sera from long ill patients with frequent exacerbations, as well as 2-3 degree of activity last exacerbation, with family history. Found a strong inverse correlation between the levels of DDR1 and IGF-1, and the line with TGF-β1 and β2-MG of blood and urine. In patients with obstructive HP DDR1 level was significantly higher than in patients with non-obstructive clinical form. Conclusions: Increased serum DDR1 shows the progression of kidney damage with active fibrogenesis and inflammation in certain categories of patients with CP in a state of clinical and laboratory remission.